Valve-in-Valve TAVR: State-of-the-Art Review. Issue 4 (August 2019) - Edelman, J. James; Khan, Jaffar M.; Rogers, Toby; Shults, Christian; Satler, Lowell F.; Ben-Dor, I. Itsik; Waksman, Ron; Thourani, Vinod H.
Abstract : An increasing number of surgically implanted bioprostheses will require re-intervention for structural valve deterioration. Valve-in-valve transcatheter aortic valve replacement (ViV TAVR) has become an alternative to reoperative surgery, currently approved for high-risk and inoperable patients. Challenges to the technique include higher rates of prosthesis–patient mismatch and coronary obstruction, compared to native valve TAVR. Herein, we review results of ViV TAVR and novel techniques to overcome the aforementioned challenges.